Hydrotropic Technique: A Promising Method to Enhance Aqueous solubility of Nimesulide and to Reduce Difficulties in Bioavailability - Gopaiah, Mr. K. Venkata (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: Nimesulide is poorly water soluble (0.1 mg/ml). The low aqueous solubility gives difficulties in bioavailability. To improve the aqueous solubility and to enhance bioavailability the hydrotropic technique were used. Materials and Methods: In this research, hydrotropes such as ascorbic acid, sodium p-hydroxy benzoate, and sodium gentisate, and sodium ascorbate were used. Solid complexes of nimesulide and hydrotropes were prepared using coprecipitation method. The precipitates were amorphous in nature. In general, solid complexes can be characterized by techniques such as melting point, infrared-spectroscopy, differential scanning calorimetry, Fourier transformed infrared spectral studies were carried out for nimesulide and hydrotropes for their pure form and their complexes. Results and Discussion: A hydrotrope solubilizes hydrophobic part of nimesulide in aqueous solutions. In general, hydrotropes consists of both hydrophilic part and a hydrophobic part in which the hydrophobic part is very small to form immediate self-aggregation. Hydrotropy is one of the solubility enhancement techniques which improve solubility to many folds with use of hydrotropes. It is one of the recognized techniques available for resolving the solubility issue in nimesulide. Conclusion: The present work investigates the solubility enhancement and hence the bioavailability of the drug. The solubility of the drug can be increased by a variety of contemporary methods such as hydrotropic solubilization and solid dispersions. Hydrotrophy refers to a solubilization process, whereby the addition of large amounts of a second solute results in an increase in the aqueous solubility of a poorly soluble compound.